SCIENTIFIC BIOGRAPHY OF ACADEMICIAN BUBUINA ORUZBAEVA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article is devoted to the life and scientific activity of the outstanding scientist honorary academician in a number of great linguists Orusbaeva Bubaina Omurzakova who dedicated her life to her native language has made an inordinate contrition to a profound study of the national language from a scientific point of view.
Keywords: linguist, turkologist , academician, dialectology, morphology, word formation